Assessing values within collaborative interventions for families with parental substance use and child welfare involvement. Issue 3 (27th May 2021) - Huebner, Ruth A.; Yan, Yueqi; Sanders, Janelle; Nix, Dara; DeCerchio, Ken; Hansen, Nancy; Young, Nancy K.
ABSTRACT: Effective intervention for families with parental substance use disorders (SUD) and child maltreatment requires multiple agencies to collaborate on system changes to deliver family-centered services. The Collaborative Values Inventory (CVI) was designed for use in multi-system interventions to facilitate understanding of differences in beliefs among professionals. This study reports on significant revisions to the CVI and the psychometrics of the CVI_2. The primary aim was to develop CVI measures suitable for research by identifying a subset of CVI_2 items with adequate factor loadings, sensitivity to interagency differences, and strong overall reliability. The Outcomes CVI includes 24-items that met the inclusion criteria and subsequently showed a strong factor structure and strong unidimensional reliability. Suggestions for research on values and beliefs for family-centered initiatives are included.